Relationship between the Operational Risk, Operations and Information Management in Russian Banking Sector - Dilyara Farilovna Zakirova; Elvira Farilovna Zakirova; Lenar Nailevich Safiullin; Bulat Ilfirovich Gatin (International Journal of Supply Chain Management, 2019)
The paper considers the issue of operational risk management in Russian commercial banks. The correlation and regression analysis also revealed the dependence of the operational risk level on liquidity risks (current and long-term liquidity ratios) and crediting risks (the amount of overdue debt, the aggregate risk for bank insiders, and reserves for possible losses on loans and equivalent debt). It has been proved that with the growth of current and long-term liquidity ratios, overdue debts and reserves for possible losses on a loan, loan debt and its equivalent ratios, the operational risks of credit organizations in Russia grow, whereas with an increase in the aggregate risk for bank insiders (H10.1), the level of operational risks of the banking sector is reduced. The values of operational risk in the banking sector of the Russian Federation are predicted on the basis of the scenario approach for 2019-2020. As part of the pessimistic and moderate growth scenario, an increase in the level of operational risks is predicted, which makes it necessary to implement new approaches to managing this type of risk in credit institutions and introduce new methods of managing operational risk by the Central Bank of the Russian Federation.